Bordetella hinzii Pneumonia and Bacteremia in a Patient with SARS-CoV-2 Infection - Maison-Fomotar, Michele; Sivasubramanian, Geetha (Emerging infectious diseases, 2021)
Patients with severe acute respiratory syndrome coronavirus 2 infection may have bacterial co-infections, including pneumonia and bacteremia. Bordetella hinzii infections are rare, may be associated with exposure to poultry, and have been reported mostly among immunocompromised patients. We describe B. hinzii pneumonia and bacteremia in a severe acute respiratory syndrome coronavirus 2 patient.